2021
DOI: 10.1016/s1474-4422(21)00031-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of lacunar stroke: a pooled analysis of individual patient data and genome-wide association studies

Abstract: Background The genetic basis of lacunar stroke is poorly understood, with a single locus on 16q24 identified to date. We sought to identify novel associations and provide mechanistic insights into the disease. MethodsWe did a pooled analysis of data from newly recruited patients with an MRI-confirmed diagnosis of lacunar stroke and existing genome-wide association studies (GWAS). Patients were recruited from hospitals in the UK as part of the UK DNA Lacunar Stroke studies 1 and 2 and from collaborators within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 83 publications
1
136
0
Order By: Relevance
“…One approach used to prioritize the likely causal gene within an associated locus with multiple genes is the use of a transcriptome-wide association study (TWAS) [ 27 ]. The TWAS from the SVS GWAS results found that the expression of SLC25A44 in the arteries and the 2q33·2 locus ( CARF , FAM117B , ICA1L , and NBEAL1 ) in the arteries and brain was causally associated with an SVS risk [ 23 ]. Very similar results regarding the 2q33·2 locus were previously obtained by Persyn et al and Sargurupremraj et al in their TWAS of WMH [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach used to prioritize the likely causal gene within an associated locus with multiple genes is the use of a transcriptome-wide association study (TWAS) [ 27 ]. The TWAS from the SVS GWAS results found that the expression of SLC25A44 in the arteries and the 2q33·2 locus ( CARF , FAM117B , ICA1L , and NBEAL1 ) in the arteries and brain was causally associated with an SVS risk [ 23 ]. Very similar results regarding the 2q33·2 locus were previously obtained by Persyn et al and Sargurupremraj et al in their TWAS of WMH [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these loci presented a nominal association ( p -value < 5 × 10 −3 ) with non-lobar ICH and SVS in the corresponding GWAS but not at a genome-wide level [ 4 ]. Three different GWAS in SVS have identified significant associations with this phenotype in 16q24.2 ( ZCCHC14 ) [ 6 ], 2q33.2 ( ICA1L and WDR12 ) [ 22 ], ULK4 ; SPI1-SLC39A13-PSMC3-RAPSN , and ZBTB14-EPB41L3 [ 23 ]. Recently, an MTAG combining SVS and WMH allowed for the identification of seven loci associated with SVS for the first time but some of them were previously associated with ICH ( SLC25A44-PMF1-BGLAP , LOX-ZNF474-LOC100505841 , FOXF2 FOXQ1 , SH3PXD2A , VTA1-GPR126 , HTRA1-ARMS2 , and COL4A2 ) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SH3PXD2A is nearby a sentinel locus for atrial fibrillation 80 and the KDELR3 region is associated with Electrocardiogram T-peak to T-end 81 , suggesting a role for heart rhythm and contractility in African ancestry blood pressure traits. SH3PXD2A is also within loci associated with intraocular pressure, cerebral small vessel disease, and white matter hyperintensities, all closely related to blood pressure levels [82][83][84] . MBTPS1 has also been implicated in stroke 85 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics of the stroke cases are shown in eTable 2. Genotypes for all studies except Helsinki were imputed using the TOPMed reference panel on the University of Michigan Imputation Server 17 . The Helsinki Study imputed genotypes using a Finnish population-specific reference panel and the BEAGLE software.…”
Section: Methodsmentioning
confidence: 99%